Respuesta :

Hello! The answer to your question would be as followed:

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

                    -79-(7*w+3*(4*w-1)=0

 -79 -  (7w +  3 • (4w - 1))  = 0

Pulling out like terms :

  Pull out like factors :

  -19w - 76  =   -19 • (w + 4)

 -19 • (w + 4)  = 0

Equations which are never true :

      Solve :    -19   =  0

This equation has no solution.

A a non-zero constant never equals zero.

Solving a Single Variable Equation :

     Solve  :    w+4 = 0

Subtract  4  from both sides of the equation :

                     w = -4

                  w = -4

Answer:

w =-4

Step-by-step explanation:

I put a picture to help

Ver imagen mirmir28